The remedy of injunction / Amirah Ali - Ali, Amirah (Faculty of Law, 1985)
The remedy of Injunction is one aspecc of the law which is alive. In the sense that it is part of law which keeps on growing like roots from a big tree. Thus building a better grip and affirms the need of law and equity. This paper is written in a an attempt to capture the development of injunction as providing one of the popular equitable remedy sought for in suits and proceeding of the court. Tracing down its history from early powers of the court and jurisdiction, the first stage of development in the classification of injunction as result to overcome the inadequacy of other remedies available at law. Finally the new types of injunction which recently developed during the past decade. Namely, the Maneva Injunction, Anton kéller Injunction and the 'Erinford Properties‘ Injunction.